MATERNAL AUTHORITY AND PATRIARCHY: INSIGHTS FROM SHASHI DESHPANDE’S THE DARK HOLDS NO TERRORS AND GITHA HARIHARAN’S THE THOUSAND FACES OF NIGHT - Arya, Rati; Kumar, Vipin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the transmission of patriarchal values across generations, with a focus on the role of maternal authority in Shashi Deshpande’s The Dark Holds No Terrors and Githa Hariharan’s The Thousand Faces of Night.The study shows how a mother can take on the role of a father, mixing caring duties with upholding traditional societal expectations. These maternal figures, influenced by their own experiences with patriarchy, play a crucial role in maintaining gendered expectations, which affects their daughters’ identities and independence. The analysis highlights the two sides of motherhood, showing how mothers can be both nurturing and controlling, which can lead to emotional distance as they focus on societal expectations and obedience. This paper looks into these dynamics and highlights how important it is to rethink maternal roles outside of patriarchal frameworks, creating opportunities for emotional connection and empowerment. This study adds to discussions about feminism by highlighting the complex aspects of motherhood in a patriarchal society.